Needs assessment of youths Involved in fish farming in Ibadan metropolis, Oyo State, Nigeria (2022)
This study examined the needs assessment of youths involved in fish farming in Ibadan Metropolis, Oyo State. Nigeria. A multi-stage sampling procedure was used to select 100 youths that were involved in fish farming in the study area. Specific objectives like personal characteristics, enterprise characteristics, accessibility to factors of production, level of involvement in fish farming, constraints to involvement in fish farming and needs towards fish farming were assessed. Data were analysed using frequencies, percentages, mean, Chi-square and Pearson Product Moment Correlation. Results of the study showed that the mean age of respondents was 25.8±6 years and 79.0% were male. About sixty percent of respondents raised both catfish and tilapia and the years of experience of respondents was 4.8±5.0 years. The result further showed that 53.0% of respondent had low access to factors of production and the level of involvement in fish farming activities was high (60.0%). Constraints to involvement in fish farming were weather conditions (x=1.52), high cost of inputs (x=1.49) and high cost of feeds (x=1.48). The needs of respondents were technical (x=29.97), information (x27.10) and agro-service (x=30.64) needs with agro-service being the major need. Chi-square result showed that scale of business (X2 =0.527, p=0.004) was significantly related to the needs of respondents. Also, respondents’ accessibility to factors of production (r=0.328, p=0.001) was significantly related to their needs. The study recommended that government at all levels should provide agro-services to fish farmers and make agriculture a business that is attractive so as to encourage youths to stay in the enterprise and achieve food security in the nation.